Japan: Economic Success and Legal System - Angelo, A H (Victoria University of Wellington Law Review, 1997)
This article is a book review of Harald Baum (ed) Japan: Economic Success and Legal System (de Gruyter, Berlin, 1997) pp i-xxii, 1-401. This book is the record of the 1995 conference on "Japan: Economic Success and Legal System" which was held at the Japanese-German Center, Berlin, Germany. The book is divided into four main parts: dispute resolution, contract in Japanese business, Japanese enterprise, and the bureaucracy in Japanese economic and legal affairs. Angelo praises the book as one that gives cause for reflection on matters of Japanese law and comparative, as well as the human condition generally.